MEMS cost analysis : from laboratory to industry - Lawes, Ronald A. (Pan Stanford Publishing, 2014)
This volume demonstrates show cost analysis can be adapted to MEMS, taking into account the wide range of processes and equipment, the major differences with the established semiconductor industry, and the presence of both large-scale, product-orientated manufacturers and small- and medium-scale foundries. The content examines the processes and equipment sufficiently for the reader to appreciate how costs arise.